Art and creative development for young children - Schirrmacher, Robert, 1946- (Albany, N.Y. : Delmar, 1998)
This book is about: Creativity; Young children as artists: A developmental view; Art and aesthetics; Providing art experiences; Roles and strategies.
Keywords: Education; Child development; Curriculum planning; Arts teaching; Child development -- United States; Art -- Study and teaching (Early childhood) -- United States; Creative ability -- United States; Creative activities and seat work; Curriculum planning -- United States